Tracing the roots of Muhammadiyah thought on the concepts of Dār Al-‘Ahdi Wa Al-Syahādah - Yuli Isdiyanto, Ilham; Muhammadi, Fauzan; Fahmiddin, Umair (Faculty of Law, University of Muhammadiyah Malang, 2022)
This paper aimed to discuss the concept of Dār Al-’Ahd Wa Al-Syahādah initiated by Muhammadiyah, which requires strong historical-normative legitimacy, so it does not necessarily lose its genealogy to be applied to the legal and constitutional system in Indonesia. The big question is how is the relationship between historical aspects and the concept of Dār Al-’Ahd Wa Al-Syahādah so that it has strong foundations to be implemented later in the state and nation. This normative-conceptual research is a historical reflective study that focuses on literacy aspects as the basis to build normative and conceptual constructions. The result reveals that the idea of ​​Dār Al-’Ahd Wa Al-Syahādah in the constellation of Pancasila is a strategy to realize Baldatun Thayyibatun wa Rabbun Ghafur state with the principle of Amar Ma’ruf Nahi Munkar. The concept of Dār Al-’Ahd Wa Al-Syahādah has a reference in Al Maun Theology which from the beginning became the basis of the movement pioneered by KH Ahmad Dahlan. Therefore, this strategy must be directed to a more concrete form and a more concrete movement to realize Baldatun Thayyibatun wa Rabbun Ghafur state.